Methods of Blood Flow Modelling - Volpert, V.; Bessonov, N.; Sequeira, A.; Simakov, S.; Vassilevskii, Yu; Volpert, V. (Mathematical modelling of natural phenomena, 2016)
This review is devoted to recent developments in blood flow modelling. It begins with the discussion of blood rheology and its non-Newtonian properties. After that we will present some modelling methods where blood is considered as a heterogeneous fluid composed of plasma and blood cells. Namely, we will describe the method of Dissipative Particle Dynamics and will present some results of blood flow modelling. The last part of this paper deals with one-dimensional global models of blood circulation. We will explain the main ideas of this approach and will present some examples of its application.